2019
DOI: 10.3390/ijerph16203813
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion, Surveillance Use, and Facebook Addiction: The Moderating Role of Narcissistic Grandiosity

Abstract: One hundred and eighty-eight participants completed the online questionnaire with items on demographics (age and gender), social exclusion, surveillance use, Facebook addiction, and narcissistic grandiosity. The findings showed that social exclusion was positively associated with Facebook addiction (B = 0.237, p < 0.001) and surveillance use was significantly positively associated with Facebook addiction (B = 0.211, p < 0.01). The surveillance use of Facebook was found to be a significant mediator between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
1
8
0
1
Order By: Relevance
“…First, the results showed that social exclusion positively predicted Internet addiction, as also captured by a limited number of past research (Lim 2019 ; Poon 2018 ). However, in the Turkish sample, while Tas and Öztosun ( 2018 ) came up with a supportive finding, another early research did not report a significant relationship between social exclusion and Internet addiction (Bagir et al 2020 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…First, the results showed that social exclusion positively predicted Internet addiction, as also captured by a limited number of past research (Lim 2019 ; Poon 2018 ). However, in the Turkish sample, while Tas and Öztosun ( 2018 ) came up with a supportive finding, another early research did not report a significant relationship between social exclusion and Internet addiction (Bagir et al 2020 ).…”
Section: Discussionmentioning
confidence: 69%
“…Although several indicators (e.g., impaired self-regulation, solitude seeking, avoiding social interactions) point out the association between social exclusion and Internet addiction, there are limited research findings on it with contradictory results. For example, a positive relationship between social exclusion and Internet addiction was revealed by some early research (Lim 2019 ; Poon 2018 ). Similarly, Tas and Öztosun ( 2018 ) concluded the positive predictor role of social exclusion on Internet addiction in a Turkish sample.…”
mentioning
confidence: 99%
“…Sheldon and Bryant [ 25 ] also pointed that some psychological circumstances, such as narcissism, may reinforce different behavioral tendencies and trigger particular SNS usage (i.e., editing photos, using hashtags). We believe that one of the reasons for this is that narcissists have strong needs for recognition and admiration [ 8 ]. Stories provides a stage for recognition and admiration, and compared to news feeds, the ephemeral characteristic of Stories makes it easier for narcissists to attract the attention of others and receive immediate responses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that narcissism is correlated with SNS addiction [ 4 , 8 , 9 ]. The results of these studies have indicated that narcissists use SNSs to showcase themselves, attract the attention of others, and display their own capabilities and feelings of superiority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation